A Technology Integration Framework and Co-operative Reflection Model for Service Learning - Maimoona, Salam (Universiti Malaysia Sarawak, (UNIMAS), 2020)
In the current era of technological advancement, ICT plays a significant role in education to enrich both teaching and learning processes. However, there is a lack of research regarding the integration and effective application of technology in service learning to identify the factors, which can possibly affect the technology integration process. In addition, research on co-operative reflection is currently limited in order to understand its outcomes from students’ overall learning perspective in the service-learning context. This study aims to propose the technology integration framework and co-operative reflection model for service learning. The Design Science Research Methodology (DSRM) has been adopted to design, develop and evaluate the proposed technology integration framework and co-operative reflection model. The first contribution of this study is a proposed framework, which comprises of three major components, that include identification of general phases for service learning (building on Kolb’s experiential learning theory); a technology support layer for all phases; and stakeholders’ involvement patterns in service learning. Findings revealed that all three main components proposed in the framework of this study are effective for technology integration in service learning. Furthermore, findings of this study also unveiled several constraints of different technologies employed in various phases (e.g. reflection) of service learning. The second contribution of this study is the proposed Co-operative Reflection Model (CRM), which offers a new approach towards group reflection and explores the synergy between co-operative reflection and knowledge-building. The proposed model was validated through a prototype system, which was assessed through a case study. Findings confirmed the presence of different levels of reflective thinking such as: 34% of co-operative reflection data was marked for creating results (level 4), 25% for referring to experience (level 2), 22% for describing experience (level 1), and 19% for developing connection between experience and theories (level 3). The presence of collaborative knowledge-building is also confirmed as 68% data of co-operative reflection was marked for different levels of knowledge-building and only 28% was marked for task coordination. Further findings of this study also confirmed that there is a significant relationship between co-operative reflection and knowledge-building, which validates the notion of knowledge-building, through co-operative reflection activity. The usability and effectiveness of prototype system was validated by using the information system success model, which was empirically evaluated by using Partial Least Square based Structural Equation Modelling (PLS-SEM) approach. Results showed that system quality, service quality and sociability quality are strong predictors of usage behavior and user satisfaction. As a conclusion, this study contributed towards technology enhanced service learning by elaborating the concept of technology integration and adoption in service learning.